Takhrij Dan Syarah Hadith of Chemistry: Use of Formaldehyde in the Preservation of Corpse - Firdaus, Reynaldi Purwantara; Dalimunthe, Reza Pahlevi (International Journal on Orange Technologies, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad ﷺ. about preserving the bodies using chemicals (hanuth). This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study is about the use of hanuth in preserving the bodies and formalin as a substitute for hanuth. In addition, several benefits of hanuth were also found, including as an ingredient for the scent of corpses at the time of the Prophet Muhammad ﷺ and also as a preservative for corpses. This study concluded that the law of preserving corpses using chemicals was permitted by the Prophet Muhammad ﷺ. based on takhrij and syarah hadith. This study recommends formaldehyde as a substitute for hanuth, because hanuth in today's times is difficult to obtain.